Partisipasi Siswa dalam Proses Pembelajaran pada Mata Pelajaran IPA di SMP Negeri 18 Palu - Datubaringan, Jein; Jamhari, Mohammad; Dhafir, Fatmah; Masrianih, Masrianih; Zainal, Syech; Nurdin, Musdalifah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe student participation in science learning at SMP Negeri 18 Palu. Student participation in science learning is considered important because it can enhance active involvement, conceptual understanding, and collaboration among students, contributing to the quality of learning. This research uses a descriptive quantitative approach with 115 students from grades VII, VIII, and IX who were selected randomly. The instrument used was a questionnaire to measure the level of student participation, and the data were analyzed using descriptive statistics. The results show that (1) student participation is categorized into five main activities: asking questions, giving opinions, discussing, working on group assignments, and presenting in front of the class. (2) Most students actively participated in these activities, with the highest participation found in discussion and presentation activities. (3) Students are more active when the material is linked to everyday life and delivered in an interesting way through visual and interactive media. Based on these findings, it can be concluded that active student participation positively contributes to the quality of science learning at SMP Negeri 18 Palu.